Photoreactive organic thin films - Sekkat, Zouheir; Knoll, Wolfgang (Amsterdam ; Boston : Academic Press, 2002)
Wolfgang Knoll is a former Directory of Polymer research at the Max Planck Institute. He is extremely well know for his research in this area. Zouheir Sekkat was a Postdoctoral researcher at Max Planck working under Professor Knoll. With Knoll's involvement, we can be confident that the best people in this field will be contributing to the reference.
Part A -- Photoisomerization and Photo-Orientation of Azobenzenes -- 1. Photoisomerization of Benzenes -- 2. Ultrafast Dynamics in the Excited States of Azo Compounds -- 3. Photo-Orientation by Photoisomerization -- Part B -- Photoisomerization in Organic Thin Films -- 4. Photoisomerization and Photo-orientation of Azo Dye in Films of Polymer: Molecualr Interaction, Free Volume, and Polymer Structural Effects -- 5. Chrial Polymers with Photoaffected Phase Behavior for Optical Data Storage -- 6. Photoisomerization in Langmuir-Blodget-Kuhn Structures -- 7. Electronic and Optical Transduction of Photoisomerization Processes at Molecualr -- and Bimolecular-Functionalized Surfaces -- Part C -- Photochemistry and Organic Nonlinear Optics -- 8. Photoisomerization Effects in Organic Nonlinear Optics: Photo-Assisted Poling and Depoling and Polarizability Switching -- 9. Photoisomerization in Polymer Films in the Presence of Electrostatic and Optical Fields -- 10. Photoassisted Poling and Photoswitching of NLO Properties of Spiropyrans and other Photochromic Molecules in Polymers and Crystals -- 11. All Optical Poling in Polymers and Applications -- 12. Photoinduced Third Order Nonlinear Optical Phenomena in Azo-Dye Polymers -- Part D -- Optical Manipulation and Memory -- 13. Photoinduced Motions in Azobenzene-Based Polymers -- 14. Surface Relief Gratings on Azobenzene-Containing Films -- 15. Dynamic Photocontrols of Molecular Organization and Motion of Materials by Two-Dimensionally Arranged Azobenzene Assemblies -- 16.3-D Data Storage and Near Field Recording -- 17. Synthesis and Applications of Amorphous Diarylethenes -- Index.
Includes bibliographical references and index.
Keywords: Photoreactive organic thin films; Photoreactive organic thin films -- Industrial applications; Electronic books